2020
DOI: 10.3384/njvet.2242-458x.1992156
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between students and class teachers in vocational education and training: ‘Safety distance is needed’

Abstract: Interaction between students and teachers is fundamental and has therefore been widely studied in education. However, there have been few studies on intensive special support being provided to vocational education and training (VET) students. Firstly, the focus of this article is on students' perceptions of interactions with their class teachers. Students (aged 17-34 years) from four Finnish vocational institutions providing intensive special support were interviewed. According to the findings, the demands stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 35 publications
(18 reference statements)
1
20
0
Order By: Relevance
“…Quite the opposite has been raised in earlier studies [28,52], as qualification has often been appraised as one of the major functions of VET, which means preparing students with skills appropriate for both the world of work and for citizenship. It seems that schools are emphasizing academic and vocational achievement instead of developing students' competencies to manage their careers [42,43,47,48], whereas students with special educational needs emphasize their personal subjective growth. Even though students with special educational needs focused on their subjective empowerment and on their socialization, they perceived the professional qualification as a tool to achieve these.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Quite the opposite has been raised in earlier studies [28,52], as qualification has often been appraised as one of the major functions of VET, which means preparing students with skills appropriate for both the world of work and for citizenship. It seems that schools are emphasizing academic and vocational achievement instead of developing students' competencies to manage their careers [42,43,47,48], whereas students with special educational needs emphasize their personal subjective growth. Even though students with special educational needs focused on their subjective empowerment and on their socialization, they perceived the professional qualification as a tool to achieve these.…”
Section: Discussionmentioning
confidence: 99%
“…We consider that the underlying value of qualitative educational research is to make schools more equitable and to ensure greater equality of opportunity and outcome [60]. This was fundamental for the study because the research was conducted with students who represent a marginal and often stigmatized group of students and who use their voice in adaptable ways [42,43]. With this premise, the narrative approach became applicable in the study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the study we observed social emotions like shame and pride as the primary emotions that are present in all communication and action (Scheff 2000(Scheff , 2003. We were motivated to the present research design by observations in our earlier studies (Ryökkynen, Pirttimaa, and Kontu 2019;Ryökkynen et al 2021). Furthermore, we found this approach to be relevant because people with special needs are often in a different social position from the rest of the population (Kauppila, Lappalainen, and Mietola 2020).…”
Section: Introductionmentioning
confidence: 91%